Mathematical Model of Water Absorption in Arrowroot Starch-Chitosan Based Bioplastic - Yusmardhany Yusuf; Fauzan Irfandy; Alit Istiani (Eksergi, 2022)
Expansion of the size of the weight of bioplastics often occurs in daily use. This phenomenon happens because the material from bioplastics can absorb significant amounts of water. This process can lead to accumulation of swelling degree. Therefore, a mathematical model is needed to quantify this mechanism to predict the dynamics of changes in the weight of bioplastics with respet to time while contact with water to help practitioners during application design for the use of bioplastics. This study aims to build a mathematical model derived from the mass sense validated by experimental data through curve fitting. The experiment was conducted by observing the rate of change in the mass of bioplastic made from starch and chitosan by measuring the change in mass concerning time immersed in water under atmospheric conditions. The immersion time was varied between 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 40,50, and 60 minutes. As a result, it can be concluded that starch-chitosan-based biofilms can absorb water up to ±10.9174 gr-water/gr-bioplastic, and also this phenomenon can be quantified by a mathematical equation that derived from mass balance with an average percent error of 1.13% and R-squared coefficient of 0.9981.